Kajian Laju Infiltrasi Ditinjau dari Perbedaan Litologi Batuan, Kemiringan Lahan dan Sifat Fisik Tanah pada DAS Sungai Pisang Kota Padang - Mendoza Mendoza; Rusli HAR (Journals Mining Engineering : Bina Tambang, 2018)
The problems of this research were illegal logging in waterheds areas,  as well as land conversion as residential area and other used thus, the disruption of the rain absorption area into the soil (infiltration). Highest of the rain caused of saturated soil and potential flooding. More other, infiltration influenced by several factor they are: rocks lithology condition, land slope and soil physical characteristic. Therefore  have to doing study about infiltration rate, infiltration zone mapping and calculation of water discharge that can be absorbed by soil. This study was conducted on 10 different point. The data that had been gotten from primary data was observation in the field, that is data of infiltration rate estimation by using double ring infiltrometer, handbor for rocks lithology, tensiometer and sand cone for measuring of soil physical characteristic. Based on processing of the data using Kostiakov method, got average of infiltration rate research area is 0.1303 cm/min, belong to the classification of absorption area is very low (<0.1-0.2 cm/min). Based the statistics analysis, the condition of rocks lithology, land slope and soil physical characteristic is very influenced toward infiltration rate. The infiltration zone mapping is devided into 6 zone, with lowest infiltration rate of 0,001002-0,082666 cm/min and the highest infiltration rate zone is 0.0610078-0.86868 cm/min. Furthermore the water  discharge that can be absorbed by soil in research area of 1.22 km2 is 78,000 m3/hr/km2 (very small).  Keywords: Infiltration Rate and Infiltration Zone , Kostiakov Method, Rocks Lithology, Land Slope, Soil Physical Characteristic